PENGEMBANGAN POTENSI EKONOMI UNGGULAN MELALUI PROGRAM KELURAHAN PRODUKTIF KOTA PASURUAN - Rifky Aldila Primasworo; Pamela Dinar Rahma (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
One of effort to contribute poverty alleviation and eradication in East Java is the Village Potential Empowerment program in Pasuruan City . It is intended as an effort to develop the superior economic potential through productive urban village program of Pasuruan. The purpose of this research is to know the economic potential of Village, to know the obstacles in developing the economic potential and to explain the strategy and the program of developing the economic potential through Productive Village Program. The results obtained from this study resulted in Stable Growth Strategy, with a strategy that is done is a stable growth strategy where the development is done in stages with targets tailored to the current conditions and more priority on the factors of strength in the form of gradual development in order to achieve available opportunities. The strategy applied is the extension of Opportunities (Strategic Increasing Investment Program and Strategic Opportunity for Employment and Enhancement Program), Community Institutional Empowerment (strategic program of community empowerment in micro scope and strategic improvement program of local government accountability), Capacity Building (strategic program of health quality improvement community and strategic improvement programs of education services)